ChemInform Abstract: Ruthenium Complexes as Precursors for Chemical Vapor‐Deposition (CVD). Issue 48 (2nd December 2014) - Gaur, Ruchi; Mishra, Lallan; Siddiqi, M. Aslam; Atakan, Burak
Abstract Review: 160 refs.